Role of Lactate Dehydrogenase in Identifying Relapse for Patients With Stage I Testicular Cancer on Surveillance. Issue 6 (23rd December 2022) - Bobrowski, Adam; Anson-Cartwright, Lynn; Kuhathaas, Kopika; Jiang, Di Maria; Chung, Peter; Bedard, Philippe; Warde, Padraig; O'Malley, Martin; Sweet, Joan; Hamilton, Robert J.
Abstract : Purpose: Tumor markers alpha-fetoprotein, human chorionic gonadotropin, and lactate dehydrogenase assume a key role in the management of testicular germ cell tumors. While alpha-fetoprotein and human chorionic gonadotropin have modest sensitivity and specificity for germ cell tumors, lactate dehydrogenase has weak sensitivity and specificity. We explored the utility of lactate dehydrogenase in identifying relapse among stage I seminomatous and nonseminomatous germ cell tumors on surveillance. Materials and Methods: Patients with a history of stage I testicular germ cell tumors were identified from a prospectively maintained database at the Princess Margaret Cancer Centre from December 1980 to May 2021 and surveyed according to established institutional algorithm guidelines. The utility of lactate dehydrogenase elevation to independently detect germ cell tumor relapse was examined. Results: Among 1, 014 seminoma and 676 nonseminomatous germ cell tumor patients, 176 and 176 patients relapsed with a median time to relapse of 13.6 and 8.9 months, respectively. Imaging alone was the most common mode of relapse detection in 144 and 74 of seminoma and nonseminomatous germ cell tumor patients, respectively. Lactate dehydrogenase was elevated in 49 cases of seminoma and 38 cases of nonseminomatous germ cell tumors at relapse, but was never the sole relapse indicator. Among 350 seminoma and 311 nonseminomatous germ cell tumor patients who never relapsed, 210 and 233, respectively, had at least 1 elevated lactate dehydrogenase value. Conclusions: Lactate dehydrogenase alone did not independently contribute to early relapse detection in stage I seminoma or nonseminomatous germ cell tumor. Elevated lactate dehydrogenase values were documented in a high proportion of nonrelapsing seminoma and nonseminomatous germ cell tumor cases.